2016
DOI: 10.1016/j.chb.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of the most commonly used external variables of TAM on students’ Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) of e-portfolios

Abstract: Engagement with e-portfolios has been shown to improve students' learning. However, what influences students to accept e-portfolios is a question that needs careful study. The purpose of this study is to investigate the influence of Self-Efficacy, Subjective Norm, Enjoyment, Computer Anxiety and Experience on students' Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) of an eportfolio system and their Behavioural Intention (BI) to use the system for learning. To do this, the study tested and used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
341
6
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(511 citation statements)
references
References 97 publications
49
341
6
24
Order By: Relevance
“…Findings also confirmed H2, PEOU of the smartphone is positively related to the intention to use a smartphone for learning. Several past studies have investigated the PEOU variable in a different context (Abdullah, Ward, & Ahmed, ; Amin, Rezaei, & Abolghasemi, ; J. Lee, Ryu, & Lee, ; Li, Sun, Yang, & Guo, ; Pookulangara & Koesler, ). For example, Pookulangara and Koesler () found that PEOU is positively related to the intention to use social networking.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also confirmed H2, PEOU of the smartphone is positively related to the intention to use a smartphone for learning. Several past studies have investigated the PEOU variable in a different context (Abdullah, Ward, & Ahmed, ; Amin, Rezaei, & Abolghasemi, ; J. Lee, Ryu, & Lee, ; Li, Sun, Yang, & Guo, ; Pookulangara & Koesler, ). For example, Pookulangara and Koesler () found that PEOU is positively related to the intention to use social networking.…”
Section: Discussionmentioning
confidence: 99%
“…These norms are often determined by perceived social pressure from others for an individual to behave in a certain way to comply with those people's views. According to the TAM, external variables such as SUBs is a determinant on both PU and PEU (Legris, Ingham, and Collerette, ; Martins, Oliveira, and Popovic, ; Abdullah, Ward, & Ahmed, ). In addition, numerous studies have found that there is a link between SUB and intention (Ajzen, ; Armitage & Conner, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…PEOU is defined as the extent to which a technology is perceived as being easy to understand and use [13]. With the user experience, in this experiment, PEOU stands for easy-learning and easy-operating [1]. We hypothesized that both of PU and PEOU reflect the users' behaviour intention.…”
Section: Tammentioning
confidence: 99%